2018
DOI: 10.1051/matecconf/201822401003
|View full text |Cite
|
Sign up to set email alerts
|

Calculating the profile of intermittent grinding wheel for the sharpening teeth of the broach

Abstract: The article shows that during the grinding of complex profile blades of metal cutting tools from tool steels, unfavorable thermodynamic conditions are created in the cutting zone and, as a result, grinding burns and cracks occur on the surface of the polished workpiece. One of the methods of controlling the temperature in the cutting zone at the final grinding operations is the use of grinding wheels with a discontinuous surface. The method of calculating the profile of the discontinuous surface of the grindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…In paper [36] by authors was proposed improvement the contact performance properties, by submitting presentation of optimization of flat grinding of titanium parts by following two parameters: the relative bearing length of the profile and the relative bearing part of the parts' surface that allow assessing the quality of the surface at the microand macro-scale. The Bogutsky, V. and all shown that during the grinding of complex profile blades of metal cutting tools from tool steels, unfavorable thermodynamic conditions are created in the cutting zone and, as a result, grinding burns and cracks occur on the surface of the polished workpiece [37]. The method of calculating the profile of the discontinuous surface of the grinding wheel presented in the article makes it possible to determine its geometric parameters taking into account the wear resistance of the grinding wheel and the heat stress of the process of treatment [37].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In paper [36] by authors was proposed improvement the contact performance properties, by submitting presentation of optimization of flat grinding of titanium parts by following two parameters: the relative bearing length of the profile and the relative bearing part of the parts' surface that allow assessing the quality of the surface at the microand macro-scale. The Bogutsky, V. and all shown that during the grinding of complex profile blades of metal cutting tools from tool steels, unfavorable thermodynamic conditions are created in the cutting zone and, as a result, grinding burns and cracks occur on the surface of the polished workpiece [37]. The method of calculating the profile of the discontinuous surface of the grinding wheel presented in the article makes it possible to determine its geometric parameters taking into account the wear resistance of the grinding wheel and the heat stress of the process of treatment [37].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Bogutsky, V. and all shown that during the grinding of complex profile blades of metal cutting tools from tool steels, unfavorable thermodynamic conditions are created in the cutting zone and, as a result, grinding burns and cracks occur on the surface of the polished workpiece [37]. The method of calculating the profile of the discontinuous surface of the grinding wheel presented in the article makes it possible to determine its geometric parameters taking into account the wear resistance of the grinding wheel and the heat stress of the process of treatment [37]. In paper [38] a vitrified bond CBN point grinding wheel with coarse grinding area slope angle θ was presented.…”
Section: Literature Reviewmentioning
confidence: 99%
“…При использовании СОТС шлифовании пористых материалов наблюдается попадание ее в поры и изменение физико-химических свойств материала[3, 7, 12, 13 и др.]. Если экспериментальные исследования формирования поверхностного слоя деталей из спеченных пористых порошковых материалов на основе железа в некоторой степени освещены в литературе, то теоретические работы, направленные на прогнозирование шероховатости, образующейся при их шлифовании, практически отсутствуют, в отличие от шлифования сплошных материалов, где выполнены значительные теоретические исследования формирования микрорельефа поверхностного слоя при шлифовании[1,6,9,11,[20][21][22][23][24]. Существующие модели основываются на копировании режущего профиля абразивных зерен при формировании шероховатости детали.…”
unclassified